Randomized Trial of Motivational Interviewing to Prevent Early Childhood Caries in Public Housing. (October 2018) - Henshaw, M.M.; Borrelli, B.; Gregorich, S.E.; Heaton, B.; Tooley, E.M.; Santo, W.; Cheng, N.F.; Rasmussen, M.; Helman, S.; Shain, S.; Garcia, R.I.
Introduction: Caries experience among preschool-age children has remained relatively unchanged for the past 2 decades, despite recently documented decreases in untreated decay. Objectives: In a community-based cluster-randomized controlled trial, a motivational interviewing (MI) intervention administered to primary caregivers was hypothesized to reduce caries increment over 2 y as compared with controls, among children aged 0 to 5 y at baseline living in public housing. Methods: Public housing residents, who served as interventionists, were trained in MI with a focus on early childhood caries prevention. All 26 eligible public housing developments were randomized to either control (quarterly clinical examinations, fluoride varnish applications, toothbrush/toothpaste, and educational brochures) or intervention (same procedures as control plus MI counseling). Quarterly MI sessions were delivered in English or Spanish over 2 y, audio recorded, and assessed for treatment fidelity. The primary outcome was the increment in dmfs (decayed, missing, and filled tooth surfaces) as assessed by clinical examination at baseline, 12 mo, and 24 mo. Secondary outcomes included caregiver oral health knowledge and child oral health behaviors (child toothbrushing and sugar-sweetened beverage intake). Baseline characteristics were compared between groups and adjusted for housing-site clusters. Longitudinal outcomes were analyzed with mixed models. Results: A total of 1, 065 children (49% female, 55% non-White, 61% Hispanic, 89% below poverty level, n = 686 control) and their caregivers were enrolled. During 2 y of follow-up, the mean dmfs increment increased in both groups; however, there were no statistically significant group differences at 24 mo or group × time interactions. The mean increase in intervention caregivers' knowledge was significantly greater than that of control, F (2, 1, 593) = 3.48, P = 0.0310, but there were no significant intervention effects on caregiver-reported child sugar-sweetened beverage intake or child toothbrushing. Conclusion: MI counseling plus intensive caries prevention activities resulted in knowledge increases but did not improve oral health behaviors or caries increment (ClinicalTrials.gov NCT01205971). Knowledge Transfer Statement: When viewed in light of the findings from the companion Pine Ridge study and other recent MI studies, the results of this study suggest that when the complex disease of early childhood caries is addressed in high-risk populations, MI is not effective, and alternative approaches are warranted.